Effect of Social Networking Sites on Students’ Engagement and Motivation in Computer Science in Bayelsa State, Nigeria - Zakana, Marie Ebifagha; Fomsi F., Esther (European Scientific Journal, ESJ, 2019)
The use of Social Networking Sites (SNS) in the classroom is not a new phenomenon in educational research. Several researchers have investigated the use of SNS and its effect on students. This study investigated the use of Edmodo and Facebook as SNS for engaging senior secondary Computer Science students in Bayelsa State, Nigeria. The study adopted quasi experimental design. Eighty (80) S.S.II Computer Science students were purposively sampled and used for the study. Two research questions were answered, and two hypotheses tested at 0.05 level of significance. The Instruments used for data collection were titled “Computer Science Achievement Test” (CSAT) and “Students’ Engagement and Motivation toward Facebook and Edmodo Questionnaire” (SEMFEQ). CSAT pre-test and post-test was made up of 40 multiple choice questions while SEMFEQ was made up of two parts (A and B) and part B was made up of two sections (A and B of 25 items each). Data collected were analyzed using mean and standard deviation to answer research questions and independent t-test was used for the hypotheses. Cronbach Alpha was used to compute the internal consistency of SEMFEQ and a reliability coefficient of 0.88 was obtained. The findings revealed of the two dependent variables in this study; engagement and motivation that the first independent variable, Facebook had a higher significant effect on senior secondary Computer Science students than Edmodo, the second independent variable. Recommendations made based on the findings amongst others include incorporating these platforms to support classroom instruction.